A method of preparing a photovoltaic cell by laser modification of a composite doped source and a photovoltaic cell

CN123021816APending Publication Date: 2026-10-30JOLYWOOD (TAIZHOU) SOLAR TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611337956.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]针对现有技术的缺陷,本发明旨在提供一种复合掺杂源激光改性制备光伏电池的方法和光伏电池,以解决现有激光选择性掺杂工艺的导电性能、抗电池衰减性能及界面结合稳定性无法兼顾、工艺流程繁琐、钝化结构易损伤、贱金属电极电池衰减严重的技术问题

Benefits of technology

目前行业内激光选择性掺杂工艺通常采用单一掺杂源体系(如硼掺杂源或磷掺杂源体系),功能单一,仅能够实现硅基底的电极接触区的导电掺杂改性,因此现有激光选择性掺杂工艺无法同时满足太阳能电池的低接触电阻、高界面稳定性、抗金属污染衰减、简易量产工艺的多重需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123021816A_ABST
    Figure CN123021816A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of solar cell manufacturing, and discloses a method for preparing a photovoltaic cell by laser modification of a composite doping source and the photovoltaic cell. The method comprises the following steps: removing a passivation layer of an electrode contact area of a cell substrate to locally expose an emitter; preparing a composite doping paste, which comprises a P-type or N-type doping source, a metal material, a dispersing agent, a binder and a solvent, and the mass ratio of the metal material to the doping source is 1:3-5; applying the composite doping paste to the surface of the exposed emitter to form a composite doping layer; performing selective treatment on the composite doping layer by using a pulse laser, so that the doping source diffuses to the surface layer of silicon to form a heavily doped silicon layer, the metal material and silicon are combined in situ to form a metal silicide barrier layer, and interface passivation repair is realized; and preparing a metal electrode. In the laser selective treatment process, the conductive heavily doped modification, in-situ growth of a metal ion barrier layer and interface defect repair passivation can be simultaneously completed, the cell performance can be improved, the process is simplified, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solar cell manufacturing technology, specifically to a method for preparing photovoltaic cells by laser modification of composite doped sources and the photovoltaic cell itself. Background Technology

[0002] Laser selective doping is a core technology for improving the electrical performance of high-efficiency crystalline silicon solar cells. The basic principle of laser selective doping is to utilize the selective heating characteristics of a laser to locally melt the metal grid contact area at high temperatures. This allows dopant atoms in the dopant source layer pre-formed on the silicon wafer surface to rapidly diffuse and dissolve in the molten silicon, thus forming a heavily doped region in the electrode contact area and retaining a lightly doped region in the non-metallic contact area. This balances the need for metal-semiconductor ohmic contact and the suppression of minority carrier recombination. Compared to traditional high-temperature furnace diffusion doping, laser selective doping offers advantages such as strong localization, low thermal damage, simple process, and compatibility with fine grid line fabrication. It is widely used in the heavy doping modification of the electrode contact area in solar cells, effectively reducing the contact resistance between the electrode and the silicon substrate and improving the fill factor and photoelectric conversion efficiency of the solar cell.

[0003] Currently, laser selective doping processes in the industry typically employ a single doping source system, namely a pure boron source (p-type doping) or phosphorus source (n-type doping) system. This system has a limited function, only capable of modifying the conductivity of the silicon substrate. In the context of current photovoltaic mass production technology iterations, this laser selective doping process using a single doping source system suffers from several unavoidable technical drawbacks: (1) Lack of metal ion blocking ability leads to severe degradation of solar cells. The heavily doped region formed by a single boron or phosphorus source is a bare silicon surface, lacking a blocking structure for the migration of metal components. During subsequent high-temperature sintering and long-term service, metal ions such as silver, aluminum, and copper in the metal electrode paste easily diffuse along grain boundaries, dislocations, and other defect channels to the silicon substrate and junction region, and introduce deep-level recombination centers in the band gap, resulting in a decrease in minority carrier lifetime and an increase in leakage current, which manifests as an aggravation of initial light-induced degradation (LID) and potential-induced degradation (PID) of the cell.

[0004] (2) Poor interfacial bonding stability and degraded electrochemical performance. During the laser melting-recrystallization process, the pyramidal textured surface of the silicon wafer collapses locally, forming a large number of dangling bonds and lattice damage. Since the doped source layer itself does not have passivation and interfacial bonding functions, and is immediately cleaned and removed after laser treatment, it is difficult to form a stable and dense chemical bonding interface between the heavily doped region and the subsequently deposited passivation film. Under the action of humid heat and electric field coupling, the interfacial state density continues to increase, the series resistance increases, and the fill factor and open circuit voltage deteriorate simultaneously.

[0005] As shown in the authorized publication numbers CN116885049B and CN110299422B, to address the aforementioned issues of metal ion diffusion and electrochemical performance stability, existing technologies typically employ multiple auxiliary processes after the laser selective doping process, such as barrier layer deposition, high-temperature annealing and curing, and post-oxidation repair, to compensate for the shortcomings of the doping source layer itself. However, these additional auxiliary processes not only increase equipment investment, manpower, and time costs, but also result in lengthy and cumbersome process steps. Furthermore, multiple global thermal processing steps (such as post-oxidation or annealing at 900~1100℃) inevitably damage the passivation structure already constructed on the battery surface—including the attenuation of hydrogen passivation effect of the alumina / silicon nitride stacked passivation film, thickening or breakdown of the back tunneling oxide layer, and deterioration of the crystallization state and passivation quality of the intrinsic polycrystalline silicon layer. This leads to a significant reduction in passivation gain, a decrease in the battery open-circuit voltage, a narrowing of efficiency improvement, or even negative gain, making it a losing proposition. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention aims to provide a method and a photovoltaic cell for laser modification using composite doping sources. This method solves the technical problems of existing laser selective doping processes, such as the inability to simultaneously achieve optimal conductivity, resistance to cell degradation, and interfacial bonding stability; cumbersome process flow; easy damage to passivation structures; and severe cell degradation due to base metal electrodes. This method leverages the advantages of laser selective doping, combined with a composite doping slurry, to simultaneously achieve three effects within a single laser selective doping step: conductive heavy doping modification, in-situ growth of a metal ion barrier layer, and passivation to repair interfacial defects. This eliminates the need for additional auxiliary processes such as barrier layer deposition and high-temperature curing, avoiding damage to the passivation structure from multiple global thermal processing steps. While ensuring high-efficiency electrical performance, it significantly improves the stability of the battery during long-term outdoor operation, simplifies mass production processes, and reduces production costs.

[0007] Based on this, the present invention discloses a method for preparing photovoltaic cells by laser modification of composite doped sources, comprising the following steps: S1. Provide a battery substrate, which includes a silicon wafer and an emitter and a passivation layer sequentially formed on the surface of the silicon wafer. Remove the passivation layer of the preset electrode contact area to partially expose the emitter, while retaining the passivation layer of the non-electrode contact area. The non-electrode contact area (corresponding to the non-laser area) is protected by masking or visual positioning. S2. Prepare a composite doping slurry; the composite doping slurry includes a doping source, a metal material, a dispersant, a binder, and a solvent; wherein the doping source is a P-type or N-type doping source, the metal material is a metal material that can form a metal silicide barrier layer with silicon, and the mass ratio of the metal material to the doping source is controlled at 1:3-5. S3. Prepare the composite doped paste on the emitter surface of the electrode contact area and dry it to form a dense, non-porous composite doped layer. S4. The composite doped layer is selectively treated with pulsed laser, so that the doping source in the composite doped layer diffuses to the emitter surface to form a heavily doped silicon layer, while the metal elements in the metal material combine with silicon in situ to form a metal silicide barrier layer, and achieve interface passivation repair. S5. Prepare a metal electrode on a metal silicide barrier layer to obtain the photovoltaic cell.

[0008] Preferably, in step S1, the battery substrate is a TOPCon (tunneling oxide passivated contact) crystalline silicon battery film or a BC (back contact) crystalline silicon battery film; the passivation layer includes a silicon nitride film and / or an aluminum oxide film; the emitter is an N-type or P-type emitter.

[0009] Preferably, in step S2, the doping source is a boron doping source or a phosphorus doping source; the composite doping paste is a Ni-B composite doping paste, a Ni-P composite doping paste, a Ti-B composite doping paste, or a Ti-P composite doping paste.

[0010] In the composite doping paste of this invention, taking Ni-B composite doping paste as an example, the mass ratio of metal material (Ni) to dopant source (B) is controlled at 1:3-5. This ensures a sufficient proportion of boron, guaranteeing high-concentration p-type heavy doping of the silicon surface and meeting the requirements for low-ohmic contact. The appropriate nickel ratio allows for sufficient reaction under laser induction to generate continuous and dense NiSi. x The barrier layer also avoids the problems of increased interfacial recombination and contact resistance caused by excessive nickel content.

[0011] More preferably, in step S2, the composite doping slurry includes metal materials, dopant sources, dispersants, binders, and solvents prepared in a mass ratio of 1:3-5:0.3-0.8:0.5-1:15-20.

[0012] More preferably, the metal material is a nano-metal powder with a particle size of 50-70 nm; the boron doping source is a borate ester or an ultrafine nano-boron powder with a particle size of 30-40 nm; the dispersant is polyvinylpyrrolidone; the binder is acrylic resin; and the solvent is anhydrous ethanol and / or terpineol.

[0013] Preferably, in step S3, the composite doped paste is deposited on the emitter surface of the electrode contact area by spin coating, spraying or screen printing to form a composite doped paste layer with a thickness of 200-500 nm; and dried at 80-120°C for 5-10 min to form the composite doped layer.

[0014] Preferably, in step S4, the pulsed laser is a nanosecond pulsed laser or a picosecond pulsed laser, with a laser wavelength of 532nm or 1064nm, a laser output power of 8-50W, a scanning speed of 5000-50000mm / s, and the scanning trajectory is aligned with the electrode grid lines in the electrode contact area.

[0015] More preferably, in step S4, the doping concentration of the heavily doped silicon layer is greater than the doping concentration of the emitter in the non-electrode contact region; the doping concentration of the heavily doped silicon layer is 1-3×10². 0 atoms / cm³, while the doping concentration of the emitter in the non-electrode contact region is 2-5×10¹. 9 atoms / cm³; the metal silicide barrier layer is NiSi. x Barrier layer or TiSi x A barrier layer is formed, and the metal silicide barrier layer is closely attached to the surface of the heavily doped silicon layer.

[0016] Preferably, in step S5, the metal electrode is at least one of a silver electrode, a copper electroplated electrode, and an aluminum electrode.

[0017] The present invention also discloses a photovoltaic cell, which is prepared by a method for preparing photovoltaic cells by laser modification of a composite doped source as described above in the present invention.

[0018] Compared with the prior art, the present invention has at least the following beneficial effects: Currently, laser selective doping processes in the industry typically employ a single doping source system (such as boron or phosphorus doping sources), which has a limited function and can only achieve conductive doping modification of the electrode contact area of ​​the silicon substrate. Therefore, existing laser selective doping processes cannot simultaneously meet the multiple requirements of solar cells, such as low contact resistance, high interface stability, resistance to metal contamination attenuation, and simple mass production processes.

[0019] Based on this, the present invention provides a method for preparing photovoltaic cells by laser modification of composite doped sources. The core of this method is to design a composite doped source precursor (including but not limited to Ni-B, Ni-P, Ti-B, Ti-P and other composite doped pastes) adapted to laser instantaneous processing. Through fixed-point pulsed laser irradiation, a single laser scan is performed in the preset electrode contact area of ​​the photovoltaic cell to simultaneously achieve in-situ growth of heavily doped and barrier alloy layers and repair of interface micro-defects. This constructs a composite protective conductive structure of "silicon substrate-heavily doped conductive layer-dense barrier layer-metal electrode". The entire process is free from global high-temperature thermal damage and requires no subsequent auxiliary processes. It can simultaneously meet the multiple requirements of low contact resistance, high interface stability, resistance to metal contamination degradation, and simple mass production process of solar cells.

[0020] Therefore, the method for preparing photovoltaic cells by laser modification using composite doping sources of this invention utilizes the advantages of selective laser doping, combined with the use of composite doping slurry (i.e., composite doping source precursor), to simultaneously achieve heavy doping through a single laser scan, thereby reducing electrode contact area resistance, growing an in-situ barrier alloy layer to resist metal contamination degradation, and repairing interface micro-defects to provide high interface stability and improve cell electrical performance, thus achieving the preparation of efficient and stable photovoltaic cells. The method of this invention is adaptable to all types of N-type and P-type crystalline silicon photovoltaic cells, compatible with various electrode processes such as silver electrodes, copper electroplated electrodes, and aluminum electrodes, and can be directly adapted to existing laser doping mass production equipment without production line modification, making it highly practical for implementation. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the structure after step S1 of the method for preparing photovoltaic cells by laser modification of composite doped sources in Example 1.

[0022] Figure 2 This is a schematic diagram of the structure after step S3 of the method for preparing photovoltaic cells by laser modification of composite doped sources in Example 1.

[0023] Figure 3 This is a screenshot of the structure of a method for preparing photovoltaic cells by laser modification of composite doped sources according to Example 1, after processing in step S5.

[0024] Reference numerals: 1. Silicon wafer; 2. Emitter; 3. Composite doped layer; 4. Heavily doped silicon layer; 5. Barrier layer; 6. Passivation layer; 7. Metal electrode. Detailed Implementation

[0025] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0026] Example 1 This embodiment describes a method for preparing photovoltaic cells using laser modification with composite doped sources. See [link to previous document]. Figure 1-3 This includes the following steps: S1. Battery Substrate Pretreatment: A TOPCon N-type crystalline silicon battery wafer (i.e., battery substrate) is selected before conventional screen printing. This battery substrate includes: a silicon wafer 1, and an emitter 2 and a passivation layer 6 sequentially formed on the front surface of the silicon wafer 1. The electrode grid contact area (referred to as the electrode contact area) on the front surface of the battery substrate is precisely located. The laser only removes the insulating passivation layer 6 (including silicon nitride film and aluminum oxide film) in the electrode contact area of ​​the battery substrate to partially expose the emitter 2, while the insulating passivation layer 6 is completely preserved in the non-electrode contact area.

[0027] S2. Preparation of the composite doping slurry: A Ni-B composite doping slurry was used as the precursor for the composite doping source. The mass ratio of Ni to B in the Ni-B composite doping slurry was controlled at 1:3.75. The Ni-B composite doping slurry, by mass, includes the following raw materials: 15 parts of nano-boron powder (30 nm particle size), 4 parts of nano-Ni powder (50 nm particle size), 2 parts of polyvinylpyrrolidone dispersant, 3 parts of acrylic resin binder, and 76 parts of anhydrous ethanol-terpineol compound solvent. The above raw materials were mixed, stirred and dispersed for 2 h, and ultrasonically defoamed for 30 min to obtain a uniform black composite doping slurry.

[0028] S3. Preparation of composite doped layer 3: Using screen printing technology and the same screen as for metallization, the prepared Ni-B composite doping paste is uniformly deposited on the preset electrode contact area of ​​the emitter 2 of the battery substrate to form a 400nm thick composite doping paste layer; then, it is dried in a chain low-temperature drying oven at 100℃ for 8 minutes until the solvent is completely evaporated, so as to obtain a uniform, dense, and non-porous composite doped layer 3 in the electrode contact area of ​​the emitter 2, without cracking or peeling defects.

[0029] S4. Laser Selective Processing: A 532 nm nanosecond pulsed green laser is used to selectively process the composite doped layer 3. Laser process parameters: laser output power of 28 W, scanning speed of 20000 mm / s, flat-top rectangular spot linewidth of 80 μm, and pulse repetition frequency of 250 kHz. The process is completed in a single scan along the preset electrode contact area, with a single laser scan simultaneously triggering boron heavy doping modification and NiSi doping in the electrode contact area. x In-situ growth and interface passivation repair of the (nickel silicide) barrier layer 5. This step utilizes a laser-induced instantaneous local high-temperature field (micron-level heating only on the surface layer, while the entire substrate remains at a low temperature) to trigger a synchronous coupling reaction. The specific process is as follows: (1) Boron heavy doping modification: The instantaneous thermal field of the laser activates the boron atoms in the composite doped layer 3, causing the boron element to diffuse rapidly and directionally to the surface of the battery substrate in the electrode contact area, so as to form a high-concentration, high-activation-rate p-type heavy doped conductive layer in the electrode contact area of ​​the emitter 2 (the doping concentration of the p-type heavy doped conductive layer is 2×10²). 0 atoms / cm³; while the doping concentration in the non-electrode contact region of emitter 2 is 2×10⁻⁶ atoms / cm³; 19 (atoms / cm³), significantly reducing electrode contact resistance; (2) In-situ growth of barrier layer 5: Relying on the instantaneous local energy excitation of pulsed laser, nickel atoms and silicon atoms at the interface undergo solid-state diffusion combination, and dense and stable NiSi is generated in-situ. x Barrier layer 5 (i.e., nickel-silicon alloy layer), the NiSi xThe barrier layer 5 is closely attached to the surface of the heavily doped silicon layer 4 (i.e., the p-type heavily doped conductive layer) to form a seamless barrier structure. (3) Interface passivation repair: Laser instantaneous thermal effect repairs micro-pores and dislocation defects generated during silicon surface doping, optimizes electrode interface contact state, reduces interface recombination loss, and improves battery electrical performance.

[0030] S5. Using screen printing technology, on NiSi x Metallic aluminum paste is printed on the barrier layer 5 and sintered in a chain sintering furnace to obtain the metal electrode 7.

[0031] After completing step S5, a photovoltaic cell of this embodiment can be obtained. For example... Figure 3 As shown, the photovoltaic cell includes: a silicon wafer 1, an emitter 2 on one surface (e.g., the front surface) of the silicon wafer 1, a heavily doped silicon layer 4 (i.e., a p-type heavily doped conductive layer) on the electrode contact region of the emitter 2, and a NiSi layer on the surface of the heavily doped silicon layer 4. x Barrier layer 5, while passivation layer 6 is provided in the non-electrode contact area of ​​emitter 2, NiSi x The barrier layer 5 is in contact with the metal electrode 7.

[0032] Example 2 This embodiment describes a method for preparing photovoltaic cells using laser modification with composite doped sources, and the photovoltaic cell itself is described below. Specifically, it refers to Embodiment 1, but differs from Embodiment 1 in that: In this embodiment, step S2 uses a Ti (titanium)-P (phosphorus) composite doping paste to replace the Ni-B composite doping paste in step S2 of embodiment 1.

[0033] In this embodiment, the mass ratio of Ti to P in the Ti-P composite doped slurry is controlled at 1:4. The Ti-P composite doped slurry, by mass, comprises the following raw materials: 16 parts of nano-red phosphorus powder (40 nm particle size), 4 parts of nano-titanium powder (70 nm particle size), 2 parts of polyvinylpyrrolidone dispersant, 3 parts of acrylic resin binder, and 75 parts of anhydrous ethanol-terpineol compound solvent. The above raw materials are mixed, stirred and dispersed for 2 h, and ultrasonically defoamed for 30 min to obtain a uniform black composite doped slurry.

[0034] In step S3 of this embodiment, the screen printing is also replaced with Ti-P composite doped paste. Therefore, the barrier layer grown in step S4 of this embodiment is TiSi. x (Titanium silicide) barrier layer.

[0035] Comparative Example 1 This comparative example describes a method for preparing photovoltaic cells using laser modification of a doped source, and the photovoltaic cell itself is described below. Specifically, it refers to Example 1, but differs from Example 1 in that: In step S2 of this comparative example, the Ni-B doped paste does not contain nano-Ni powder, and 4 parts of nano-boron powder (particle size 30 nm) are added to make up for the missing nano-Ni powder; the rest are the same as in Example 1.

[0036] Comparative Example 2 This comparative example describes a method for preparing photovoltaic cells using laser modification with composite doped sources, and the photovoltaic cell itself is described below. Specifically, it refers to Example 1, but differs from Example 1 in that: In the composite doping slurry of step S2 in this comparative example, the mass ratio of nano-Ni powder (particle size 50 nm) to nano-boron powder (particle size 30 nm) is controlled at 1:2, and the sum of their mass fractions remains unchanged; the rest are the same as in Example 1.

[0037] Comparative Example 3 This comparative example describes a method for preparing photovoltaic cells using laser modification with composite doped sources, and the photovoltaic cell itself is described below. Specifically, it refers to Example 1, but differs from Example 1 in that: In the composite doping slurry of step S2 in this comparative example, the mass ratio of nano-Ni powder (particle size 50 nm) to nano-boron powder (particle size 30 nm) is controlled at 1:6, and the sum of their mass fractions remains unchanged; the rest are the same as in Example 1.

[0038] Performance testing The electrical performance, contact resistivity, and metal composite properties of the photovoltaic cells prepared in Examples 1-2 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1 below. In Table 1, Eta is the photoelectric conversion efficiency, Uoc is the open-circuit voltage, Isc is the short-circuit current, FF is the fill factor, and J0,metal is the metal composite.

[0039] Table 1

[0040] Referring to Table 1, we can see that: (1) Example 1 is the application of Ni-B composite doping paste with a Ni:B mass ratio of 1:3.75 as a composite doping source in synchronous laser modification of p-type silicon. In this Ni-B composite doping paste, B provides a p-type heavy doping source. Since B atoms are smaller, they can better enter the lattice of crystalline silicon through laser doping compared to Ni, thus forming a heavily doped silicon layer (p-type heavily doped conductive layer) in the electrode contact region of the emitter; while Ni and the substrate silicon can form a nickel-silicon alloy to form a dense NiSi at the interface of the heavily doped silicon layer. x The barrier layer can effectively resist the damage to the substrate caused by the aluminum spikes of the metal electrode and reduce metal composite, as can be seen from the J0,metal metal composite data in Table 1.

[0041] Example 2 illustrates the application of a Ti-P composite doped paste with a Ti:P mass ratio of 1:4 as a composite doping source in synchrotron laser modification of N-type silicon. In this Ti-P composite doped paste, P provides a heavily doped N-type source, and Ti and Si form a titanium-silicon alloy layer (TiSi). x The barrier layer prevents the penetration of aluminum paste. The photoelectric conversion efficiency of 27.19% shows that the Ti-P composite doping source can be well applied to the N-type substrate of aluminum paste metallization.

[0042] Moreover, as can be seen from Table 1, the photovoltaic cells prepared in Examples 1-2 have good electrode contact performance, low metal recombination and better electrical performance (such as Eta, Uoc, Isc, FF).

[0043] (2) Comparative Example 1 uses pure B-doped paste. Compared with others, it has a single heavy doping effect, so its contact resistance is low. However, due to the lack of atomic doping to form a barrier layer, the aluminum paste can easily cause severe lattice damage to the substrate, introduce a large number of deep-level recombination centers, and bring about high metal recombination. Its J0,metal is the highest, reaching 270 fA / cm. 2. Furthermore, the battery electrical performance (such as Eta, Uoc, Isc, FF) of Comparative Example 1 is significantly inferior to that of Example 1.

[0044] (3) The nickel-boron mass ratio in the Ni-B composite doped paste of Comparative Example 2 is too high, at 1:2. The excessive Ni component forms an overly thick and dense barrier layer. In addition, the insufficient doping source causes the contact resistance to rise rapidly. The deterioration of electrode contact performance will directly affect the FF, ultimately leading to a reduction in the photoelectric conversion efficiency of the battery.

[0045] (4) In Comparative Example 3, the nickel-boron mass ratio in the Ni-B composite doped slurry was too low, at 1:6. The insufficient Ni content was similar to that in Comparative Example 1, resulting in high metal recombination. Excessive metal recombination directly affected the open-circuit voltage of the battery, ultimately leading to a decrease in the battery's photoelectric conversion efficiency. It is noteworthy that the decrease in photoelectric conversion efficiency of Comparative Example 3 was less than that of Comparative Example 1, indicating that the nickel-silicon alloy (NiSi...)... x The formation of the barrier layer also repairs the defects at the interface to some extent and plays a certain role in inhibiting interface recombination.

[0046] In summary, only by adjusting the ratio of metal material to dopant source in the composite doping paste to an appropriate level can the three core functions be simultaneously achieved in the laser selective processing: first, sufficient dopant source to construct a heavily doped layer on the silicon surface of the electrode contact area, reducing the metal-to-silicon contact resistance; second, generation of a continuous and complete silicide barrier layer to block high-temperature penetration of aluminum atoms and suppress interfacial carrier recombination; and third, the instantaneous thermal effect of the laser to repair microscopic pores and dislocation defects generated during silicon surface doping, optimizing the electrode interface contact state, reducing interfacial recombination losses, and improving the battery's electrical performance. If the mass ratio of metal material to dopant source in the composite doping paste deviates from the optimal range, defects such as insufficient doping or discontinuous barrier layer may occur, making it impossible to simultaneously achieve low contact resistance and low J0,metal, ultimately limiting the battery's photoelectric conversion performance.

[0047] Although preferred embodiments of the present invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present invention.

[0048] The technical solution provided by the present invention has been described in detail above. Specific examples have been used to illustrate the principle and implementation of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core idea of ​​the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation and application scope based on the idea of ​​the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A method for preparing photovoltaic cells by laser modification with composite doped sources, characterized in that, Includes the following steps: S1. Provide a battery substrate, the battery substrate including a silicon wafer and an emitter and a passivation layer sequentially formed on the surface of the silicon wafer, removing the passivation layer in the preset electrode contact area to partially expose the emitter, while retaining the passivation layer in the non-electrode contact area. S2. Prepare a composite doping slurry; the composite doping slurry includes a doping source, a metal material, a dispersant, a binder, and a solvent; wherein the doping source is a P-type or N-type doping source, the metal material is a metal material that can form a metal silicide barrier layer with silicon, and the mass ratio of the metal material to the doping source is controlled at 1:3-5. S3. Prepare the composite doped paste on the emitter surface of the electrode contact area and dry it to form a dense, non-porous composite doped layer. S4. The composite doped layer is selectively treated with pulsed laser, so that the doping source in the composite doped layer diffuses to the emitter surface to form a heavily doped silicon layer, while the metal elements in the metal material combine with silicon in situ to form a metal silicide barrier layer, and achieve interface passivation repair. S5. Prepare a metal electrode on a metal silicide barrier layer to obtain the photovoltaic cell.

2. The method for preparing photovoltaic cells by laser modification of composite doped sources according to claim 1, characterized in that, In step S1, the battery substrate is a TOPCon crystalline silicon battery film or a BC crystalline silicon battery film; the passivation layer includes a silicon nitride film and / or an aluminum oxide film; the emitter is an N-type or P-type emitter.

3. The method for preparing photovoltaic cells by laser modification of composite doped sources according to claim 1, characterized in that, In step S2, the doping source is a boron doping source or a phosphorus doping source; the composite doping paste is a Ni-B composite doping paste, a Ni-P composite doping paste, a Ti-B composite doping paste, or a Ti-P composite doping paste.

4. The method for preparing photovoltaic cells by laser modification of composite doped sources according to claim 3, characterized in that, In step S2, the composite doped slurry includes metal materials, dopant sources, dispersants, binders and solvents prepared in a mass ratio of 1:3-5:0.3-0.8:0.5-1:15-20.

5. The method for preparing photovoltaic cells by laser modification of composite doped sources according to claim 4, characterized in that, The metal material is a nano-metal powder with a particle size of 50-70 nm; the boron doping source is a borate ester or an ultrafine nano-boron powder with a particle size of 30-40 nm; the dispersant is polyvinylpyrrolidone; the binder is acrylic resin; and the solvent is anhydrous ethanol and / or terpineol.

6. The method for preparing photovoltaic cells by laser modification of composite doped sources according to claim 1, characterized in that, In step S3, the composite doped paste is deposited on the emitter surface of the electrode contact area by spin coating, spraying or screen printing to form a composite doped paste layer with a thickness of 200-500 nm; and dried at 80-120℃ for 5-10 min to form the composite doped layer.

7. The method for preparing photovoltaic cells by laser modification of composite doped sources according to claim 1, characterized in that, In step S4, the pulsed laser is a nanosecond pulsed laser or a picosecond pulsed laser, with a laser wavelength of 532nm or 1064nm, a laser output power of 8-50W, a scanning speed of 5000-50000mm / s, and the scanning trajectory is aligned with the electrode grid lines in the electrode contact area.

8. A method for preparing photovoltaic cells by laser modification of composite doped sources according to claim 1 or 7, characterized in that, In step S4, the doping concentration of the heavily doped silicon layer is greater than the doping concentration of the emitter in the non-electrode contact region; the doping concentration of the heavily doped silicon layer is 1-3×10². 0 atoms / cm³, while the doping concentration of the emitter in the non-electrode contact region is 2-5×10¹. 9 atoms / cm³; the metal silicide barrier layer is NiSi. x Barrier layer or TiSi x A barrier layer is formed, and the metal silicide barrier layer is closely attached to the surface of the heavily doped silicon layer.

9. The method for preparing photovoltaic cells by laser modification of composite doped sources according to claim 1, characterized in that, In step S5, the metal electrode is at least one of a silver electrode, a copper electroplated electrode, and an aluminum electrode.

10. A photovoltaic cell, characterized in that, It is prepared by a method for preparing photovoltaic cells using a composite doped source laser modification as described in any one of claims 1-9.

Citation Information

Patent Citations

  • A laser-induced boron-doped selective emitter TOPCon structure solar cell and its fabrication method

    CN110299422B

  • A laser doping method and TOPCon solar cells

    CN116885049B